1998
DOI: 10.1111/j.1365-2621.1998.tb17925.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Listeria monocytogenes in Vacuum‐Packaged Pre‐Peeled Potatoes

Abstract: Growth of Listeria monocytogenes on the surface of fresh peeled potatoes, treated with sulfite or a commercial browning inhibitor (CBI), packaged under vacuum and stored at 4, 15 and 28°C was determined. At 4°C, L. monocytogenes did not grow in all treated potatoes even after 21 days. At 15°C, L. monocytogenes grew to 7 log 10 CFU/g within 12 days in the potatoes treated with sulfite or CBI. At 28°C, L. monocytogenes population was greater than 3 log 10 CFU/g by 24 h in all samples regardless of treatment. Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…No effect of packaging material choice on the growth of L. monocytogenes on the potato slices or the composite meals could be detected. The finding that the potato slices did not support the growth of L. monocytogenes corresponds with findings from Juneja, who found no significant growth of L. monocytogenes on inoculated potato slices stored under refrigeration for up to 21 days. It should be noted though that in this research the slices were stored at 4°C.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No effect of packaging material choice on the growth of L. monocytogenes on the potato slices or the composite meals could be detected. The finding that the potato slices did not support the growth of L. monocytogenes corresponds with findings from Juneja, who found no significant growth of L. monocytogenes on inoculated potato slices stored under refrigeration for up to 21 days. It should be noted though that in this research the slices were stored at 4°C.…”
Section: Discussionsupporting
confidence: 85%
“…Ubiquitous and persistent in food‐processing environments, it may occur in food products due to postcontamination . If the pathogen is not adequately inactivated by heating the food before consumption, this will pose a health risk to the consumer …”
Section: Introductionmentioning
confidence: 99%
“…Currently, processors must list preservatives used and their concentration on forms when filing their processes with the FDA. However, results of several studies have indicated that preservative acids, including benzoate, sorbate, and sulfite, contributed to killing pathogenic bacteria in foods (8,9,11,18). A comparative study of the relative concentrations of organic acids needed for a 5-log reduction of E. coli 0157:H 7 at pH 3.2 revealed that benzoic and sorbic acids were significantly more effective than common food acids (citric, malic, lactic, and acetic) for killing bacterial pathogens, based on equimolar protonated acid concentrations (13).…”
Section: Ec Se Lmmentioning
confidence: 98%
“…Nelle patate sbucciate, inoculate con L. monocytogenes e confezionate sotto vuoto in buste a elevata barriera, a 4°C per 21 giorni non si osservava crescita, ma a 15°C il batterio arrivava a 7 log 10 /g in 12 giorni 53 . A 10°C la crescita si verificava in tutti i campioni, tranne nelle carote grattugiate.…”
Section: Listeria Monocytogenesunclassified